Uridine as a novel fuel for cancer cells - Dhar, Ruby; Arun Kumar,; Subhradip Karmakar, (Asian Journal of Medical Sciences, 2023)
Cancer cells are known to have an enormous appetite for calorie. This is something they are addicted to sustain their unrestricted growth and rapid proliferation. In order to accomplish this feat, cancer cells has evolved multiple mechanisms, rewiring their metabolic circuitry such that metabolic fuels are preferentially diverted to meet their energy demands. A classic example (Warburg effect) of this is aerobic glycolysis and preferential production of lactate to produce ATP (without relying on mitochondrial oxidative phosphorylation). Further, rapid proliferation of cancer cells, exhausts the nutrient and oxygen supply derived from the existing vasculature, making them hypoxic. In turn triggers the upregulation of pro angiogenic factors from the hypoxic tumor sites( HIF), which in turn re-vascularizes the tumor mass, bringing in metabolic cargo. When it comes to cancer metabolism, cancer cells are highly innovative to devise novel mechanisms to bypass metabolic regulations and In a recent article published in Nature Metabolism, Skinner et al. identified an unusual source of glucose in cancer cells. Ribose moiety of uridine can be repurposed to replenish the energy requirements in cancer cells thorough the uridine phosphorylase UPP1/UPP2 mediated cleavage of uridine into its constituents , uracil and ribose-1-phosphate (R1P). R1P is then utilized to convert into fructose-6-P and glyceraldehyde-3-P by the non-oxidative branch of the HMP shunt back to glycolysis and ATP production. These findings are novel and intuitive. It means that the cancer cells has the ability to salvage glucose from uridine, when needed. This also indicates that cutting off Uridine supply to cancer cells maybe a mechanism to target cancer cells .